Effect of the capital Sufficiency in evaluating the Banking and financial performance - عباس كاظم جاسم الدعمي; مروج طاهر هذال (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to identify the impact of capital adequacy in the financial performance indicators. A sample selected from the Iraqi private banks amounted to 14 banks, a period of (10 years), from year (2005) until year (2014). The main hypothesis of research is that the positive and strong relationship between these indicators and financial performance banking important in achieving banking superior financial performance, which can attention to the independent variables (capital adequacy indicators) that directly impact in promoting financial performance indicators, which will reflect positively on the various aspects of the local economy, and thus can mitigate the effects of the various crises that can be exposed to if we have a sound banking sector of the Iraqi economy. They have reached the researchers at the end of their search to a set of conclusions, including the disparity study sample banks in the ratio of capital to total assets, and this marks the great disparity in the adoption of administrative, regulatory and investment frameworks, especially when we consider that the increase in the proportion of capital to total assets hurt in the interest of the depositors it provides them with protection against risks, but it reduces and limits the profitability of shareholders and investors in banks.